Kajian Sanitasi terminal di Provinsi Daerah Istimewa Yogyakarta Tahun 2016 - Dani Febriyanto; Haryono Haryono; Purwanto Purwanto (Sanitasi: Jurnal Kesehatan Lingkungan, 2017)
Sanitation is an attempt to oversee some physical environmental factors that affect humans, especially for things that have deleterious effects, to physical development, health, and life survival.Based on the preliminary test conducted on 2 to 4 April 2016, it was revealed that there weresome facilities that did not comply with the requirements. This condition has bad impact on theenvironment and human health. The purpose of this study was to describe the sanitation condition of bus stations in Yogyakarta Province by conducting survey study with descriptive analysis.From the population of 16 bus-stations located in the province, as the sample were Wates BusStation, Jombor Bus-Station, Giwangan Bus-Station and Dhaksinarga Bus station which wereselected by using are probability sampling method. There were five variables under study whichwere observed by doing sanitation inspection, i.e. outdoor environment, indoor and building, sanitation facilities, comfort and safety, and food and drink hygiene. Based on the study results, itcan be concluded that sanitation condition in bus-stations in Yogyakarta is still not good, sinceonly Giwangan Bus-Station that can be categorised as properly healhty, with 89 % compliance.